ANALISIS YURIDIS PENANGANAN TINDAK PIDANA PENCURIAN OLEH ANAK DI BAWAH UMUR BERDASARKAN UU SISTEM PERADILAN PIDANA ANAK - Hakim, Arief Rachman; Ambarini , Shera Tri; Pinggala , Waode; Afrianda, Charlina Retno Puteri; Prasetya , Syalaizha Febtria Putri (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2024)
Handling criminal acts of theft by minors is an important issue in the juvenile criminal justice system in Indonesia. Based on the Juvenile Criminal Justice System Law, the handling of this case must consider aspects of restorative justice and protection of children's rights. This research aims to analyze how the juvenile criminal justice system regulates the legal process for children who commit the crime of theft. This study examines the approach implemented in the law, including the diversion process, the role of justice institutions, and rehabilitation efforts for juvenile offenders. The Juvenile Criminal Justice System Law emphasizes the importance of rehabilitation and reintegration of children into society, as well as reducing the use of prison sentences as the main solution. This research also discusses the challenges faced in implementing this policy, such as the lack of rehabilitation facilities and public awareness of the importance of a more humane approach. It is hoped that this analysis will provide insight for policy makers and legal practitioners in improving the handling of cases of theft by minors in a fairer and more effective way.